Lithofacies And Depositional Environment Of Halang Formation On Part Of Cihikeu River Section, Majalengka, North Java - Wijaya, Eric; Abdurrokhim, .; Helmi, Faisal; Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2017)
AbstractThis study about lithofacies and depositional environment is located at Cihikeu River, Village Area of Mekarwangi Village, Bantarujeg District, Majalengka, West Java. Geographically, the research area is located at 60 56’ 11,7” latitude and 60 57’ 09,3” latitude and 1080 11’ 22,3” BT until 1080 12’ 20,3” BT. Based on Arjawinangun Geological Map (Djuri, 1995), the research area is located at Upper Parts of Halang Formation. This research show that the lithology that dominantly occur in the research area is sandstones, mudstones, and breccia.The methods that been used in this research are stratigraphics cross section measurements, lithofacies analysis, and based on secondary data which is paleontology analysis, it can be concluded that there are 8 lithofacies refers to the submarine facies classification by Stow, 1985 that occur in research area, which are facies A1-1, facies A1-3, facies B1-1, facies C2-2, facies C2-3, facies E1-1, facies E2-1, and facies F2-2. Based on the secondary data, the age of research area can be concluded into middle miocene to late miocene.Based on the lithofacies analysis, the lithofacies association concluded into 3 lithofacies association, which are FA-1, FA-2, and FA-3. From those lithofacies associaton characteristics, thereafter the depositional environment can be interpretated into 4 sub-depositional environments which are lower slope, upper fan, middle fan, and lower fan that refers to submarine depositional environments classification by Walker, 1984. Keywords : Lithofacies, Lithofacies association, Depositional environments, Submarine fan